Pemberdayaan Masyarakat dalam Budidaya Kangkung Darat Berbasis Pemanfaatan Sampah Rumah Tangga - Muhammad Ferdi Kurniawan; Victor Bintang Panunggul; Muh. Nakkir; Husen Bahasoan; Kadir Kadir (Abdibaraya, 2026)
The accumulation of household organic waste and the limited use of productive home yards remain key challenges for rural communities. This community service program aimed to enhance community capacity in land-water spinach cultivation by utilizing household waste through a multidisciplinary approach. The program was implemented using the Participatory Action Research (PAR) method and involved 30 participants from a farmer group and Family Welfare Empowerment members in the partner village. The activity stages included problem identification; training on producing liquid organic fertilizer and eco-enzyme from domestic waste; practical cultivation of land water spinach using recycled containers; training on recording production costs and calculating Cost of Goods Sold; and digital marketing assistance through social media and e-commerce platforms. Program effectiveness was measured using pre-test and post-test instruments and N-Gain Score analysis across four aspects: organic fertilizer engineering, cultivation skills, agribusiness financial literacy, and digital marketing readiness. The evaluation results showed an increase in participants’ capacity, with an average N-Gain Score of 0.80, which falls into the high category. The greatest improvement was observed in agrotechnology at 0.86, followed by chemical engineering at 0.81, informatics at 0.80, and business management at 0.73. These findings indicate that integrating household waste processing, vegetable cultivation, business management, and digital marketing can strengthen community independence in developing a productive, environmentally friendly, and economically valuable home-yard farming system.